Masonic parallels in Mabini's true decalogue and constitutional program - Gealogo, Francis A. (Philippine studies : historical and ethnographic viewpoints, 2019)
"Apolinario Mabini's True Decalogue and the Constitutional Program of the Philippine Republic reflected some parallelisms with ideas derived from Freemasonry. Being a Mason, Mabini wrote the two texts with the end in view of transforming the moral, philosophical, and political framework of Philippine society and government that was being born through the revolution. This research note analyzes the two texts as well as the ideas that Mabini expressed in them and compares them with Masonic texts, particularly the Código Moral Masónico, one of the guiding moral and philosophical books of nineteenth-century Freemasonry."